Shared-photodetector readout to improve the sensitivity of positron emission tomography. (9th October 2018) - Du, Junwei; Peng, Peng; Bai, Xiaowei; Cherry, Simon R
Abstract: Sensitivity is an important performance characteristic of positron emission tomography (PET) systems. Improved sensitivity can be used to reduce injected dose, reduce scan time, or improve the signal-to-noise ratio and temporal resolution for dynamic studies. One way to improve the sensitivity of PET scanners is to reduce the gaps between detector modules. In this paper, a new signal processing method, named the shared-photodetector readout method, is proposed and evaluated. In this method, the signals generated in nearest neighbor photodetectors adjacent to the detector module of interest, were used to help identify the interaction location in the detector module of interest. Using this method, scintillator array-based detector modules with almost 100% packing fraction can be built, and the edge crystals can be clearly resolved, even when the crystals are small compared to the photodetector size. To evaluate this signal processing concept in one dimension, a detector block with four dual-ended readout detector modules, was designed. The detector block consisted of eight 4 × 4 arrays of SensL MicroFJ-30035 SiPMs coupled to both ends of a 14 × 56 array of 0.9 × 0.9 × 20 mm 3 LYSO elements with a pitch size of 0.96 mm and a length of 20 mm. Performance in terms of energy resolution, flood histogram, timing resolution and depth-of-interaction resolution obtained using the shared-photodetector readout method were compared to those obtained using a conventional readout method. The results show that better over-all performance was achieved using the shared-photodetector readout method, especially at the edges and corners of the array.